2018
DOI: 10.1093/ee/nvy077
|View full text |Cite
|
Sign up to set email alerts
|

Floral Resource Competition Between Honey Bees and Wild Bees: Is There Clear Evidence and Can We Guide Management and Conservation?

Abstract: Supporting managed honey bees by pasturing in natural landscapes has come under review due to concerns that honey bees could negatively impact the survival of wild bees through competition for floral resources. Critique and assessment of the existing body of published literature against our criteria focussing on studies that can support best management resulted in 19 experimental papers. Indirect measures of competition examining foraging patterns and behavior yielded equivocal results. Direct measures of repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 79 publications
3
55
0
Order By: Relevance
“…This has implications for assessing competition between native bees and honeybees (Wojcik et al. ), because relative abundance of honeybees to native bees recorded will vary depending on the survey method used.…”
Section: Discussionmentioning
confidence: 99%
“…This has implications for assessing competition between native bees and honeybees (Wojcik et al. ), because relative abundance of honeybees to native bees recorded will vary depending on the survey method used.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies showed that honeybees may compete with wild bees and other pollinators for resources (Henry and Rodet , Wojcik et al. ). The presence of honeybees within our sites may have changed the visitation rate and occurrence of other pollinators on our experimental plant plots.…”
Section: Discussionmentioning
confidence: 99%
“…These two morphological groups of Apidae and honey bees have similar dietary requirements, exploiting the same floral resources (pollen and nectar) [17,36]. As summarized in Wojcik et al 2018 [37], previous studies have found that adding honey bee colonies could negatively affect wild bees and particularly bumblebees especially due to this overlap in resource use. On the contrary, flies, syrphids and butterflies do not exclusively rely on floral resources, especially during their larval life-stage, which might explain the absence of negative interactions with honey bees [38].…”
Section: Discussionmentioning
confidence: 99%